Amines functionalized C60 as solid base catalysts for Knoevenagel condensation with high activity and stability. Issue 105 (12th October 2015) - Sun, Yongbin; Cao, Changyan; Huang, Peipei; Yang, Shuliang; Song, Weiguo
Abstract : Amines functionalized C60 were prepared through a simple amination reaction of C60 with organic amines, and they showed high activity and stability for Knoevenagel condensation. Abstract : Four kinds of amines functionalized C60 were prepared through an amination reaction of C60 with organic amines. Their surface structures and basic properties were studied by Fourier transform infrared spectrometry (FTIR), X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption (TPD) with CO2 as the probe molecule. When used as solid base catalysts, N -aminoethylpiperazine functionalized C60 (C60 -AEP ) showed the best catalytic activity in the Knoevenagel condensation reaction due to the highest basic strength. In addition, theC60 -AEP catalyst also showed impressive catalytic stability. All these features endowedC60 -AEP with characteristics of both homogeneous and heterogeneous catalysts. More interestingly, chirall -lysine functionalized C60 (C60 -L-L ) can be used for asymmetric intermolecular aldol reactions.